Identification of Children of Mentally Ill Patients and Provision of Support According to the Norwegian Health Legislation: A 11-Year Review - Reedtz, Charlotte; Jensaas, Eva; Storjord, Trine; Kristensen, Kjersti Bergum; Lauritzen, Camilla (Frontiers in Psychiatry, 2022)
Background: According to amended legislation implemented in Norway in 2010, personnel in healthcare services for adults are obligated to identify patients’ minor children and to assess the family situation. Health personnel is also obligated to contribute to adequate support to families affected by parental mental illness or substance use disorders. The intention behind the amendment was to support and protect children of mentally ill parents, as they are at risk of developing problems of their own. The aim of the present study was to evaluate health personnel’s practice during the years 2010-2020, more specifically; a) to what extent children of patients with mental illness and substance use disorders are registered in patient records, and b) to what extent activities relating to the assessment and support of patients’ minor children are documented in patient records. Method: The participants in the study are patients admitted to Division for Mental Health and Substance Use at the University Hospital of North Norway in the years 2010 - 2020. The data was drawn from patient records during October 2021. Results: The registration of patients’ minor children is considerably strengthened since the introduction of the new Norwegian Health Personnel Act in 2010, and estimates show that 56% of patients’ minor children are identified. However, only 31% of cases where patients have identified minor children this result in health personnel performing activities to support the children. Discussion: Based on the rising proportion of identified minor children throughout the ten-year period, it seems evident that the dissemination efforts have contributed to the development of some new skills among health personnel. However, compared with the national estimation that 35% of mentally ill and substance abusing patients have minor children, a large proportion of children remains unidentified. After identification, there seem to still be a long way to go before minor children are systematically offered support. Different solutions to strengthen the implementation of new skills in clinical practice, to ensure the identification of minor children and provision of necessary support for them is discussed.